Representasi Peran Domestik Wanita dalam Film Parasite - Flamy Beauty Domestika (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this study was to find out how representative the domestic role of women in the film Parasite is. The research method uses qualitative research with John Fiske's semiotic analysis method with a focus on seeing and being able to describe the representation of women's domestic roles in the Parasite film in terms of the audio visual displayed in the film, there are women's domestic roles based on three levels in John Fiske's semiotics, namely reality level, representation level and ideology level. The results of this study are the reality level showing the female character as a character that is in accordance with Mrs. Park's character as a good mother and wife. This representative level uses camera settings, lighting, and music. And the ideological level displays strong social inequality in this film and the role of women is closed because it is more focused on social inequality. The conclusion of this study is that the representation of the domestic role of women has 3 levels of Jhon Fiskes' semiotic analysis, namely the level of reality, the level of representation, and the level of ideology. Keyword: Female Domestic Roles, Parasite Movie, Representation.